Iteration convergence condition modeling for single spaceborne SAR image direct positioning. Issue 4 (1st October 2016) - Dong, Yuting; Zhang, Lu; Liao, Mingsheng
Abstract: Single SAR image direct positioning is to determine the ground coordinate for each pixel in the SAR image assisted with a reference DEM. During this procedure, an iterative procedure is essentially needed to solve the uncertainty in elevation of each pixel in the SAR image. However, such an iterative procedure may suffer from the problem of divergence in shaded and serious layover areas. To investigate this problem, we performed a theoretical analysis on the convergence conditions that has not been intensively studied till now. The Range-Doppler (RD) model was simplified and then the general surface is degenerated into a planar surface. Mathematical deduction was then carried out to derive the convergence conditions and the impact factors for the convergence speed were evaluated. The theoretical findings were validated by experiments for both simulated and real scenarios.